CONCEPTS OF LEGAL ORDER: HISTORY AND MODERNITY - LIPEN S.V. (Legal Bulletin)
The article discusses various options for understanding the legal order - one of the important categories of theoretical legal science. The relevance of the problems of the article is due, on the one hand, to drawing attention to the category of “legal order” as one of the characteristics of the Russian legal system, on the other hand - insufficient systematic development of historical approaches to the study of the legal order. The main goal of this work is to identify the patterns of historical development of conceptual approaches to the study of the legal order. The problems under consideration. The article analyzes approaches to understanding the legal order, grounded in the political and legal doctrines of the XVII-XX centuries, in Soviet and modern legal science. The methods used. The study was conducted on the basis of modern general scientific methodology. Along with general scientific methods, formal dogmatic, sociological, historical, axiological and other approaches were also used.